Visual Anchoring: Fixed-Wing UAS Orbit Stabilization About a Visual Anchor Point Without GPS Dependence - Grimes, Ryan James (My University, 2018)
This paper describes a system for stabilizing an orbit of an unmanned aircraft system (UAS) around a target. The system utilizes an inner/outer loop controller architecture to achieve a stabilized, coordinated turn orbit about a point. The innovation is that the primary inputs to this controller are obtained from a vision system that computes the slant range to the target based on images streamed from the aircraft making vision the primary sensor modality for achieving a stabilized orbit. Both the vision system for estimating slant range and the associated controller for achieving a stabilized orbit are discussed. Varying levels of simulation including software-in-the-loop (SITL) are presented before discussing flight testing of the custom built UAS.
Thesis (Master's)--University of Washington, 2018
Keywords: anchoring; denied; GPS; orbit; UAS; visual; Aerospace engineering; Aeronautics and astronautics